Gender inequality and contradictions in West African development: the need for centriarchy (2004)
The convergence and almost absolute uniformity among communities in West Africa on the issue of gender inequity remains one of the central challenges of globalisation. The centrality of this phenomenon is given that women constitute almost 50% of the population in most of these societies. Hence, any policy or convention or culture that inflicts poverty on women, unwittingly overburdens their men counterparts to the extent society "crashes". The feminization of poverty in a patriarchal structure has led to over-arching consequences impinging negatively on the education of women, their access to credit facilities and other resources and their general involvement in the process of decision making in the family. In some communities women only achieve status and recognition through children, especially males, making some of them engage in child bearing even in conditions that threaten their lives. In addition, although the practice of Female Genital Mutilation [FGM) is widely discouraged as harmful, some cultures in the sub-region still attach great significance to it. These translate into poverty, which in West Africa is conceived as gender-biased. This paper argues that interventions should focus on the role of policymakers and social policy in effecting necessary attitudinal and behavioral change. This study by not only suggesting how "commonizeton" of knowledge of the factors that heighten vulnerability of women to poverty can be achieved, but also how social policies within the diversity of these societies can succeed sets out to provoke meaningful dialogue among scholars towards ideological, theoretical and policy consensus to meet the immediate challenge of enthroning gender equality in the sub-region through centriarchy.